Technical Notes Shear-Wave Velocity of Cemented Soils of Jakarta - Widjojo A. Prakoso (Jurnal Teknik Sipil, 2011)
Abstrak. Dalam rangka pengembangan korelasi antara kecepatan rambat gelombang geser vs dan tahanan penetrasi standar N-SPT untuk tanah Indonesia, hasil dari uji penetrasi standar dan uji seismic downhole dari tiga lokasi di daerah Jakarta dikumpulkan dan dianalisis. Fokus dari makalah ini adalah tanah tersementasi. Hasil dari kedua jenis pengujian digunakan untuk mengembangkan korelasi vs "“ N-SPT. Korelasi tersebut kemudian dibandingkan dengan korelasi yang terdapat di dalam literatur. Abstract. To initiate the development of shear-wave velocity vs and standard penetration resistance N-SPT correlations of soils from Indonesia, the results of standard penetration tests and seismic down hole tests from three locations in Jakarta area are compiled and analyzed. The focus of the present paper is on cemented soils. The results of the tests are used to develop a vs "“ N-SPT correlation. The results and the associated correlation are then compared to existing correlations available in the literature.